Osteomyelitis of the mandible associated with osteopetrosis: Report of a case. - Lawoyin, D.O.; Daramola, J.O.; Ajagbe, H.A.; Nyako, E.A.; Lawoyin, J.O. (My University, 1988)
A 45-year-old Nigerian housewife with chronic osteomyelitis associated with osteopetrosis is described and discussed. Haematological and radiographical investigations on routine admission led to the secondary diagnosis of osteopetrosis. To our knowledge, this is the first case of osteomyelitis of jaws associated with osteopetrosis reported in an African. © 1988.
Keywords: EMTREE medical terms: adult; Albers Schoenberg disease; article; case report; female; human; jaw disease; osteomyelitis; pathologic fracture; pathology; MeSH: Case Report; Female; Fractures, Spontaneous; Human; Mandibular Diseases; Mandibular Injuries; Middle Age; Osteomyelitis; Osteopetrosis Medline is the source for the MeSH terms of this document.